Current trends and opportunities for halal restaurants in Thailand: a conceptual framework - Wannasupchue, Wannasiri; Othman, Mohhidin; Ungku Zainal Abidin, Ungku Fatimah; Che Ishak, Farah Adibah; Mohamad, Siti Fatimah (Human Resource Management Academic Research Society, 2019)
The food and beverage business is a vital part of the tourism sector. This was among the top five sources of income for Thailand, worth 448 billion baht in 2015, and may continually increase due to the expansion of the tourism industry. More than 20 million tourists visit Thailand every year, so tourist attractions should have a variety of restaurants that should not only have food that tastes great, but also excellent service and hygienic conditions. Therefore, halal certification for food services is required when halal tourism becomes significant. Having halal status would provide a competitive advantage and accommodate the expanding market share among Muslim and non-Muslim customers. However, there is an emerging opportunity for halal restaurants, with the number of halal establishments in some regions of Thailand being inadequate for people who want to try halal food. Furthermore, some halal restaurants run by Muslim owners are not certified by a halal certification body. The objectives of this paper are to review literature on halal certification and to provide recommendations and guidelines on the opportunities in establishing a halal restaurant in Thailand. Finally, we will look into the importance of the halal status in attracting more Muslim and non-Muslim restaurant owners who have not been certified halal yet to apply for the certification.